Stereotactic Body Radiotherapy Versus Metastasectomy in Patients With Pulmonary Metastases From Soft Tissue Sarcoma - Tetta, C.; Londero, F.; Micali, L.R.; Parise, G.; Algargoush, A.T.; Algargoosh, M.; Albisinni, U.; Maessen, J.G.; Gelsomino, S. (Clinical oncology (Royal College of Radiologists (Great Britain)), 2020)
The lung is the preferred site of metastasis from soft tissue sarcoma (STS). This systematic review aims to evaluate the outcomes of stereotactic body radiotherapy (SBRT) and metastasectomy (MTS) for the treatment of lung metastases from STS. A systematic review was carried out according to the PRISMA protocol. PubMed, Medline, EMBASE, Cochrane Library, Ovid and Web of Knowledge databases were searched for English-language articles to December 2018 using a predefined strategy. Retrieved studies were independently screened and rated for relevance. Data were extracted by two researchers. In total, there were 1306 patients with STS: 1104 underwent MTS and 202 had SBRT. The mean age ranged from 40 to 55.8 years in the MTS group and from 47.9 to 64 years in the SBRT group. The cumulative death rate was 72% (95% confidence interval 59–85%) in the MTS group and 56% (38–74%) in the SBRT group. The cumulative mean overall survival time was 46.7 months (36.4–57.0%) in the MTS group and 47.6 months (33.7–61.5%) in the SBRT group. The cumulative rate of patients alive with disease was 5% (2–9%) in the MTS group and 15% (6–36%) in the SBRT group. Finally, the cumulative rate of patients alive without disease in the two groups was 19% (9–29%) and 20% (10–50%), respectively. Our study showed that local treatment of pulmonary metastases from STS with SBRT, compared with surgery, was associated with a lower cumulative overall death rate and similar overall survival time and survival rates without disease. By contrast, SBRT was associated with a higher survival rate with disease than MTS. Large randomised trials are necessary to confirm these findings and to establish whether SBRT may be a reliable option for early stage disease.